Practices in and attitudes towards staff vetting in children's residential centres in the Republic of Ireland - Catherine Hanly (Scottish Journal of Residential Child Care)
This paper documents a summary of research which was conducted as part of the requirements for the completion of an MA in Child, Family and Community Studies at Dublin Institute of Technology. The aim of the study was twofold; to explore the practices of residential child care centre managers in vetting staff for employment in residential child care, and to explore the attitudes of these managers towards current vetting requirements in the Republic of Ireland. A wide range of literature exists documenting all aspects of residential care provision for young people under the age of eighteen in state care. The material examined for the purposes of this research covers both Irish and UK perspectives as well as international practice and experience in the area. This literature has consistently highlighted the particular vulnerability of this group of young people. Also highlighted in within the literature is the need for a range of safeguarding measures for these young people because of this identified vulnerability. Not least amongst these measures are comprehensive vetting practices which have been highlighted particularly through various Inquiry reports both in the UK and Ireland (Warner, 1992; Department of Health, 1994; Department of Health 1996; Corby et al., 2001). The literature review undertaken for this study demonstrated that there has been little direct research conducted on vetting either in Ireland or elsewhere and, in particular research that examines the views of those responsible for this task.